2019
DOI: 10.1016/j.ebiom.2019.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Temporal association of the development of oropharyngeal microbiota with early life wheeze in a population-based birth cohort

Abstract: Background A critical window in infancy has been proposed, during which the microbiota may affect subsequent health. The longitudinal development of the oropharyngeal microbiota is under-studied and may be associated with early-life wheeze. We aimed to investigate the temporal association of the development of the oropharyngeal microbiota with early-life wheeze. Methods A population-based birth cohort based in London, UK was followed for 24 months. We collected orophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…Our data indirectly support the notion of the important role of the gut microbiome. The overall evidence on gut microbiota suggests that a more rapid maturation is associated with decreased asthma risk and that specific genera may be associated with protection (including Veillonella, Lachnospira, Rothia and Bifidobacterium ), 30 whilst others (such as Moraxella 27 or Neisseria 31 ) increase the risk. Our findings in relation to eczema are consistent with studies which have demonstrated the importance of fecal microbiota in eczema 32 and the findings that relative abundance of immunomodulatory gut bacteria in the first year of life is associated with subsequent development of IgE‐associated eczema 33 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data indirectly support the notion of the important role of the gut microbiome. The overall evidence on gut microbiota suggests that a more rapid maturation is associated with decreased asthma risk and that specific genera may be associated with protection (including Veillonella, Lachnospira, Rothia and Bifidobacterium ), 30 whilst others (such as Moraxella 27 or Neisseria 31 ) increase the risk. Our findings in relation to eczema are consistent with studies which have demonstrated the importance of fecal microbiota in eczema 32 and the findings that relative abundance of immunomodulatory gut bacteria in the first year of life is associated with subsequent development of IgE‐associated eczema 33 …”
Section: Discussionsupporting
confidence: 86%
“…This suggests an early‐life “window of opportunity” when colonization has a potentially critical impact on health and disease 37,38 . The temporal changes in microbiota may be important, and recent study has shown that there may be a time window before age 1 year in which colonization of the oropharynx with Neisseria is positively, and with Granulicatella species negatively, associated with subsequent wheezing 31 …”
Section: Discussionmentioning
confidence: 99%
“…We, however, did not observe an association of airway bacterial carriage with asthma at school age. Prospective cohort studies that used microbiome analyses showed an association of a high abundance of Streptococcus, but not Moraxella with wheeze at age 5 or 10 years 21,22 . Differences in findings, especially with regard to the association of hypopharyngeal bacterial carriage with lower respiratory tract infections and asthma between our study and the Danish study, might be explained by the higher prevalence of lower respiratory tract infections in their cohort and assessment of asthma at an earlier age.…”
Section: Discussioncontrasting
confidence: 76%
“…10,11 In addition, detection of specific bacteria by culture (Streptococcus pneumoniae, Moraxella catarrhalis, or Haemophilus influenzae) or 16S sequencing (eg, Prevotella, Veillonella) in oral or nasopharyngeal aspirates of babies have been related to asthma in early childhood. 2,12,13 In an Australian birth cohort (Childhood Asthma Study) using bacterial metagenomics based on 16S rRNA, predominance of S pneumoniae, M catarrhalis, or H influenzae was found to interact with early allergic sensitization to increase the risk of later asthma. 3,7 Others have found coassociation between eosinophil counts, severe RV bronchiolitis, and a Haemophilusor Moraxella-dominated profile of nasopharyngeal microbiota in infants.…”
mentioning
confidence: 99%